PENERAPAN ALGORITMA BOYER MOORE PADA AUTOMATIC LINK PADA CONTENT WEBSITE - Didik Didik; Guidio L Ginting (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Building a website requires a good plan so that the website can be used effectively and efficiently. The stages carried out in building a website are started by collecting data then studying the data, then planning is carried out which is then poured in the form of a design, then the design is developed and carried out. In building a website, it certainly has its own problems, such as interface display, data processing, performance, interaction with users, and others. To build a website that has a lot of menus, is a problem for builders, because the space to place a menu will be very limited if it is aimed at devices that have a small display such as a cellphone. The algorithm in the string matching method used in this study is the Boyer Moore algorithm, this algorithm is considered the most efficient general application algorithm, the Boyer Moore algorithm includes the most efficient string matching algorithm.Keywords: String Matching Search, Boyer Moore